Study on the quality of life and the factors influencing it in elderly patients - Zhang Mei-Yan; Bi Huai-Mei; Wang Tao; Zhang Gui-Lan (Sciendo, 2018)
A society of advanced age is arriving with the increasing number of elderly patients. Little attention has been paid to the quality of life of elderly patients, which is decreasing gradually. This article aims to study the quality of life among elderly patients and explore the factors influencing it, in addition to exploring effective ways to improve the quality of life of elderly patients.